CONTENT OF READING MATERIAL ON THE EIGHTH GRADE STUDENTS’ TEXTBOOK - David Ricardo Sianipar; Siti Wina Putri Lubis; Vienna Christanty Limbong; Dewi Sartika Sianturi; Sri Ninta Tarigan (BIP: Jurnal Bahasa Indonesia Prima, 2020)
Textbook gives a big contribution to the students’ improvement in teaching process. One of the contents on the English textbook is reading. A good content of reading has several criteria. The criteria can be a clear explanation, easily to be understood, and giving new information to the students. This research aims to find out whether the content of textbook especially in reading materials fulfills criteria of good content. In conducting this research, interview and content analysis method were used to collect the data about the reading content on the textbook. After conducting the research, there were several findings about the reading content of the textbook such as the reading materials were implemented by using any various forms and perspective of English teachers of the school about the textbook. Briefly, content of textbook especially reading material contributes bigly to the students in order to enhance their skill in reading any kinds of text and other forms of reading material.